2005
DOI: 10.1111/j.1445-2197.2005.03368.x
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Ileus: Rare and Still Controversial

Abstract: One-stage procedure prevents from cholangitis, cholecystitis and recurrent ileus caused by further gallstones but bears the risk of enteric or biliary leakage after fistula closure. It should therefore be reserved for patients presenting in good general condition with a low degree of cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 28 publications
1
99
0
13
Order By: Relevance
“…Kallya Rajgopal Shenoy years, plain abdominal radiographs had remained the gold standard in the diagnosis of gallstone ileus with classical Rigler's triad of pneumobilia, presence of ectopic gallstone and mechanical bowel obstruction. However, Rigler's triad has been shown to be present in less than half of the patients with gallstone ileus, and there are recent reports advocating early use of other imaging modalities like abdominal ultrasound (US) and computed tomography (CT) scans for early diagnosis [4].…”
Section: Images In Surgerymentioning
confidence: 99%
“…Kallya Rajgopal Shenoy years, plain abdominal radiographs had remained the gold standard in the diagnosis of gallstone ileus with classical Rigler's triad of pneumobilia, presence of ectopic gallstone and mechanical bowel obstruction. However, Rigler's triad has been shown to be present in less than half of the patients with gallstone ileus, and there are recent reports advocating early use of other imaging modalities like abdominal ultrasound (US) and computed tomography (CT) scans for early diagnosis [4].…”
Section: Images In Surgerymentioning
confidence: 99%
“…In the literature, the presence of the Rigler triad on plain film radiography ranges from 17% to 87%. 12,13,18 Abdominal ultrasound can identify the presence of a cholecystoenteric fistula as well as a stone lodged in the small bowel, and when combined with abdominal radiography, can increase diagnostic sensitivity to 74%. 13,18,19 In a prospective study, Yu et al 20 showed computed tomography to have a sensitivity of 93%, a specificity of 100%, and a diagnostic accuracy of 99% for gallstone ileus.…”
Section: -11mentioning
confidence: 99%
“…Up to one-third of patients have no history of biliary colic symptomatology, and up to one-half have no history of gallbladder disease. 9,12,13 Symptoms are usually present for 3 to 5 days before presentation to a medical facility. [11][12][13][14][15][16] Once evaluated by a physician, the time to surgical treatment has a reported delay of another 3.7 days due to delay in diagnosis.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation
“…CT-scan, performed after administration of intravenous, oral and rectal contrast and reconstructed in the coronal plane, shows a large gallstone (arrow) with central calcifi cation located in the proximal jejunum. Additionally, air in the biliary system (open arrow), and in the collapsed gallbladder (arrow head) can be observed rates, since most patients present acutely, diagnosis is frequently delayed and patients have pre-existing co-morbid medical conditions [2].…”
Section: Introductionmentioning
confidence: 99%